Analisa Statik dan Optimasi Size Chassis Bus Medium dengan Metode Elemen Hingga - Kurdi, Ojo (ROTASI, 2020)
Chassis is the main component in the bus. In chassis, various types of failures occur due to static or dynamic loading conditions. In this study, the characteristics of static loads were analyzed using the FE method, and after analysis, continued with size optimization. Analysis is done to get stress and displacement with the condition of analysis in the form of two bumped wheels. After the analysis is done, the next step is to look for a factor of safety from the stress of the results of analysis. Stress and displacement analysis results, are then used to determine the constraints used in the optimization process on the chassis. Optimization is done to get the most optimum thickness on the chassis, displacement, and stress. Then compare the safety factors of all data analysis and optimization results, to get the best chassis structure.